The potential of short-chain fatty acids-producing probiotics as a treatment for liver disease: a systematic review - Nur Azizah; Muhamad Rizqy Fadhillah; Nurul Gusti Khatimah; Rizky Clarinta Putri; Clara Riski Amanda; Fadilah, Fadilah; Oswari, Hanifah; Sjatha, Fithriyah (Published by Universitas Gadjah Mada, 2025)
Recent insights reveal that liver diseases influence not only hepatic function but also disrupt gut microbial balance through the gut–liver axis. The gut–liver axis establishes a bidirectional relationship between the intestines and the liver, allowing microbial by-products such as short-chain fatty acids (SCFAs) to influence liver function and health. Short-chain fatty acids are known to maintain intestinal epithelial integrity, reduce inflammation, and support liver function. Probiotic bacteria including Lactobacillus, Bifidobacterium, and Clostridium, are natural SCFA producers and may offer therapeutic potential for liver disease by targeting the gut-liver axis. This systematic review was conducted using the PRISMA 2020 methodology to identify and evaluate preclinical studies examining the impact of SCFA-producing probiotics on liver disease. We searched PubMed, Scopus, and Google Scholar from August to October 2023, using predefined inclusion criteria based on the PICO framework. The SYRCLE risk of bias tool was employed to evaluate potential biases. A total of 14 animal studies fulfilled the inclusion criteria and were incorporated into the final analysis. The included studies demonstrated that SCFA-producing probiotics improved liver function by reducing serum liver enzymes (ALT, AST), increasing tight junction proteins (occluding, ZO-1), modulating pro-inflammatory cytokines (IL-1β, IL-6, TNF-α,), and improving lipid metabolism. These outcomes were mediated by increases in SCFA levels and improved gut barrier integrity in models of NAFLD, ALD, NASH, and autoimmune hepatitis. These findings support the promising potential of SCFA-producing probiotics as adjunctive therapies for liver disease through modulation of the microbiota-gut-liver axis. Yet, continued research is needed to determine strain-specific efficacy, optimal dosage, long-term safety, and clinical applicability. Future research should also explore personalized probiotic strategies and the integration of probiotic therapy into standard liver disease management.